BLDC motor driven electric skateboard using SVPWM - R. Palanisamy; Th. Ankit Singh; Anamika Ranjan; Jatin Singh (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Several problems are faced by today’s generation. One of them is the increase in pollution in our everyday life. Each of us can play a part in reducing this by using some environmentally friendly method such as cycles which requires mechanical force. Another way to accomplish this is by using electricity to produce this mechanical force i.e. electric motor. In this paper BLDC motor driven electric skateboard is designed with mathematical calculation, verified with simulation and developed as a experimental setup.